Prognostic Models for 9-Month Mortality in Tuberculous Meningitis. (26th September 2017) - Thao, Le Thi Phuong; Heemskerk, A Dorothee; Geskus, Ronald B; Mai, Nguyen Thi Hoang; Ha, Dang Thi Minh; Chau, Tran Thi Hong; Phu, Nguyen Hoan; Chau, Nguyen Van Vinh; Caws, Maxine; Lan, Nguyen Huu; Thu, Do Dang Anh; Thuong, Nguyen Thuy Thuong; et al.
Abstract : Prognostic models developed and validated using data from 1699 adults with tuberculous meningitis (TBM), with or without human immunodeficiency virus infection, performed well and could be used in clinical practice to identify patients with TBM at high risk of death. Abstract: Background: Tuberculous meningitis (TBM) is the most severe form of extrapulmonary tuberculosis. We developed and validated prognostic models for 9-month mortality in adults with TBM, with or without human immunodeficiency virus (HIV) infection. Methods: We included 1699 subjects from 4 randomized clinical trials and 1 prospective observational study conducted at 2 major referral hospitals in Southern Vietnam from 2001–2015. Modeling was based on multivariable Cox proportional hazards regression. The final prognostic models were validated internally and temporally and were displayed using nomograms and a Web-based app (https://thaole.shinyapps.io/tbmapp/ ). Results: 951 HIV-uninfected and 748 HIV-infected subjects with TBM were included; 219 of 951 (23.0%) and 384 of 748 (51.3%) died during 9-month follow-up. Common predictors for increased mortality in both populations were higher Medical Research Council (MRC) disease severity grade and lower cerebrospinal fluid lymphocyte cell count. In HIV-uninfected subjects, older age, previous tuberculosis, not receiving adjunctive dexamethasone, and focal neurological signs were additional risk factors; in HIV-infected subjects, lower weight, lower peripheral blood CD4 cell count, and abnormal plasma sodium were additional risk factors. The areas under the receiver operating characteristic curves (AUCs) for the final prognostic models were 0.77 (HIV-uninfected population) and 0.78 (HIV-infected population), demonstrating better discrimination than the MRC grade (AUC, 0.66 and 0.70) or Glasgow Coma Scale score (AUC, 0.68 and 0.71) alone. Conclusions: The developed models showed good performance and could be used in clinical practice to assist physicians in identifying patients with TBM at high risk of death and with increased need of supportive care.